ANTI-TUMOR ACTIVITY OF DENDRITIC CELLS IN HEALTHY DONORS AND PATIENTS WITH BRAIN TUMORS - E. R. Chernykh; O. Yu. Leplina; T. V. Tyrinova; M. A. Tikhonova; V. V. Stupak; S. V. Mishinov; I. V. Pendyurin; A. A. Ostanin (Медицинская иммунология, 2014)
In present work, a comparative analysis of cytostatic and cytotoxic activity of IL-4 and IFNα-induced dendritic cells (IL-4- and IFN-DCs) has been performed in healthy donors and patients with brain tumors. Cytostatic activity was evaluated, as a capacity of DCs to inhibit growth of NK-resistant HEp-2 and A-549 tumor cell lines, whereas cytotoxic activity was measured by assessment of HEp-2 lysis. As compared with IL4-DC, IFN-DCs from healthy donors displayed a more pronounced cytostatic effect and similar cytotoxic activity against HEp-2 cells. In the patients with brain tumors, IFN-DCs were characterized by decreased cytotoxic activity. Meanwhile, DCs from the patients with malignant gliomas virtually did not exhibit a cytotoxic potential, whereas IFN-DCs from the patients with benign brain tumors retained their cytotoxic properties. A comparative study has shown that, in contrast to healthy donors, IFN-DCs from the patients with either malignant or benign brain tumors did not inhibit HEp-2 proliferation. The loss of DC-mediated cytostatic activity was not associated with decrease of CD123+ DCs (known as cells with maximal tumor-inhibitory potential), and, most likely, it resulted from functional changes in IFN-DC populations.